Double Auction for Joint Channel and Power Allocation in Cognitive Radio Networks. (8th May 2015) - Zhou, Wei; Jing, Tao; Huo, Yan; Qian, Jin; Li, Zhen
Abstract : Auction mechanism has been widely applied to cognitive radio networks to motivate spectrum redistribution among unlicensed users and spectrum holders, in which unlicensed users with cognitive radio capability can access the licensed spectrum by compensating spectrum holders with monetary payment. However, most of prior studies on auction are mainly restricted to channel allocation with the assumption of fixed transmitting power and/or neglecting spectrum holders' interference restrictions. Few of them jointly considers the channel and power allocation. Additionally, power allocation may cause non-identical interference relationships among unlicensed users due to the variable interference ranges. In this paper, we propose two truthful double auction schemes under single-channel demand and multi-channel demand, respectively. We theoretically prove that the two auction schemes both achieve the desired economic properties. Results from numerical evaluation demonstrate our analysis.